2020
DOI: 10.1155/2020/7573103
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Exacerbates Allergic Inflammation in an Ovalbumin-Induced Mouse Model of Allergic Rhinitis

Abstract: Purpose. Bisphenol A (BPA) is found in many plastic products and is thus a common environmental endocrine disruptor. Plastic-related health problems, including allergic diseases, are attracting increasing attention. However, few experimental studies have explored the effect of BPA on allergic rhinitis (AR). We explore whether BPA was directly related to the allergic inflammation induced by ovalbumin (OVA) in AR mice. Methods. We first constructed OVA-induced mouse model, and after BPA administration, we evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…IgE is the significant biomarker of allergic diseases including allergic asthma and AR. IgE can bind with the high affinity IgE receptor on the surface of mast cells and basophils to sensitize them and start the secretion of inflammatory mediators such as leukotriene and histamine when exposed to the same allergen again (Kim et al., 2018; Li et al., 2018; Wang et al., 2020). IgE is a significant biomarker to scrutinize the efficiency of anti‐allergic drugs and scrutinize the possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IgE is the significant biomarker of allergic diseases including allergic asthma and AR. IgE can bind with the high affinity IgE receptor on the surface of mast cells and basophils to sensitize them and start the secretion of inflammatory mediators such as leukotriene and histamine when exposed to the same allergen again (Kim et al., 2018; Li et al., 2018; Wang et al., 2020). IgE is a significant biomarker to scrutinize the efficiency of anti‐allergic drugs and scrutinize the possible mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, IL‐4, a significant cytokine of up‐regulating IgE, IFN‐γ is an anti‐allergic factor of respiratory tract and biological antagonist of IL‐4 synthesis. In the development and activation of eosinophils, IL‐5 plays a critical function, increased survival time and is a significant marker in the delayed phase of hypersensitivity (Chen, Chan, et al., 2020; Piao et al., 2020; Wang et al., 2020). Airway hyper responsiveness requires IL‐5‐mediated eosinophil infiltration in the trachea (Chen, Chan, et al., 2020; Piao et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AR has been induced in mice after IP injections of OVA on days 0, 7 and 14, followed by its intranasal applications twice a day for three weeks (8,17) . Bisphenol A (BPA) has been reported to exacerbate allergic inflammation in an ovalbumin-dependent AR mouse model (18) . In this study, BPA was given to mice after they received ovalbumin IP on days 0, 7 and 14. it was reported that allergic symptoms of AR were exacerbated and serum levels of OVA-specific IgE levels increased in mice (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Bisphenol A (BPA) has been reported to exacerbate allergic inflammation in an ovalbumin-dependent AR mouse model (18) . In this study, BPA was given to mice after they received ovalbumin IP on days 0, 7 and 14. it was reported that allergic symptoms of AR were exacerbated and serum levels of OVA-specific IgE levels increased in mice (18) . In a study that investigating the effect of mesenchymal stem cells of human umbilical cord in AR treatment, IP ovalbumin was given to mice on the 0,7, and 14 th days to induce AR (19) .…”
Section: Discussionmentioning
confidence: 99%